A prospective randomised controlled trial comparing tracheal intubation plus manual in‐line stabilisation of the cervical spine using the Macintosh laryngoscope vs the McGrath® Series 5 videolaryngoscope. (2nd August 2014) - Ilyas, S.; Symons, J.; Bradley, W. P. L.; Segal, R.; Taylor, H.; Lee, K.; Balkin, M.; Bain, C.; Ng, I.
Summary Cervical spine immobilisation can make direct laryngoscopy difficult, which might lead to airway complications. This randomised control trial compared the time to successful intubation using either the Macintosh laryngoscope or the McGrath® Series 5 videolaryngoscope in 128 patients who had cervical immobilisation applied. Intubation difficulty score, Cormack & Lehane laryngoscopic view, intubation failures, changes in cardiovascular variables and the incidence of any complications were recorded. The mean (SD) successful intubation time with the Macintosh laryngoscope was significantly shorter compared with the McGrath laryngoscope, 50.0 (32.6) s vs 82.7 (80.0) s, respectively (p = 0.0003), despite the McGrath laryngoscope's having a lower intubation difficulty score and a superior glottic view. There were five McGrath laryngoscope intubation failures, three owing to difficulty in passing the tracheal tube and two to equipment malfunction. Equipment malfunction is a major concern as a reliable intubating device is vital when faced with an airway crisis.